2008
DOI: 10.1111/j.1745-9133.2008.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Accountability, Efficiency, and Effectiveness in Corrections: Shining a Light on the Black Box of Prison Systems*

Abstract: Between 1980 and 2005, the number of federal and state prisoners grew by over 350% in the United States, from 319,598 to 1, 446,269 (Bureau of Justice Statistics, 2007;Harrison and Beck, 2006). According to one international comparison, prison populations have been increasing around the world, but the increase has been more dramatic in America, which results in the country holding roughly one fifth of all people held in penal institutions worldwide (Walmsley, 2005). Such growth is unprecedented in the history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…Indeed, much like prisons themselves (see, for example, Mears, 2008), prison visitation still operates largely as a black box in which the most proximate social and relational effects of prison visits have largely escaped direct empirical scrutiny. Indeed, much like prisons themselves (see, for example, Mears, 2008), prison visitation still operates largely as a black box in which the most proximate social and relational effects of prison visits have largely escaped direct empirical scrutiny.…”
mentioning
confidence: 99%
“…Indeed, much like prisons themselves (see, for example, Mears, 2008), prison visitation still operates largely as a black box in which the most proximate social and relational effects of prison visits have largely escaped direct empirical scrutiny. Indeed, much like prisons themselves (see, for example, Mears, 2008), prison visitation still operates largely as a black box in which the most proximate social and relational effects of prison visits have largely escaped direct empirical scrutiny.…”
mentioning
confidence: 99%
“…Much of what happens in criminal justice occurs within a "black box" (Mears, 2008). The almost inevitable result is that needless errors in judgment occur that impose substantial costs on individuals and society.…”
Section: Resultsmentioning
confidence: 99%
“…More typically, however, they treat decision making as a black box and instead focus on whether various activities that should be undertaken actually are (Gaes, Camp, Nelson, & Saylor, 2004;Hatry, 2007;Mears, 2008). Put differently, performance monitoring-an empirically-based approach to monitoring program and policy implementation and associated outcomes-tends to ignore decision making.…”
Section: Introductionmentioning
confidence: 94%
“…Although these different studies cover a great deal of terrain, the truth is that they barely skim the surface of the research that is needed on what happens in prisons (Adams 1992;Mears 2008) and how prison experiences and prisoner views affect inmate behavior and prison order (Bottoms 1999) and reentry outcomes (Visher & Travis 2011). The studies here touched on inmate adjustment and victimization, visitation, gangs, programming, inmate perceptions, spatial and temporal variation in rehabilitative efforts and prison management, and more.…”
mentioning
confidence: 98%
“…Their review drew attention to the fact that criminological studies have long suggested that prison is criminogenic and to the corresponding fact that little empirical research exists that describes the prison experience or how it affects inmate behavior, whether in the short term (while in prison) or in the long term (after release). Other scholars have emphasized this problem, noting that much of what occurs in prisons does so within a "black box" (Mears 2008). That is, the day-to-day experiences, the programming and services, the treatment of inmates, the abuse of inmates or of staff, the effects of incarceration for inmates' families, and more-these all remain understudied or unstudied.…”
mentioning
confidence: 98%